Bridging Imagination Gaps on the Path to Purchase with Augmented Reality: Field and Experimental Evidence. Issue 2 (May 2022) - Hilken, Tim; Heller, Jonas; Keeling, Debbie I.; Chylinski, Mathew; Mahr, Dominik; de Ruyter, Ko
Many firms use augmented reality (AR) that projects lifelike product holograms into the physical environment to assist customers in bridging so-called "imagination gaps, " which can arise on their path to purchase. However, research has not yet studied whether and how AR might help customers address two pertinent sources of such imagination gaps: (1) increased cognitive load when evaluating multiple products together (e.g., in a bundle) and (2) extended physical distance to the point-of-sale (e.g., out-of-store, at home). Building on mental imagery theorizing, we explain how AR supports customers in bridging these gaps, and, through a series of field and experimental studies, we evidence effects on customer purchase intentions and behavior. Specifically, we show that AR-generated imagery of bundled (versus individual) products enhances intended and actual purchases at the point-of-sale. Furthermore, when deployed at distant points in the purchase funnel (out-of-store, at-home), AR increases purchases through improved self-projection, which we describe as the psychological mechanism customers use to mentally bridge distance to the point-of-sale. We qualify this mediating mechanism through an important moderating process, where the effect of AR-generated imagery on self-projection is suppressed for customers with a holistic (versus analytic) thinking style.